All Days 2011
DOI: 10.2118/143512-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Simulation Studies of Different Modes of CO2 Injection in Fractured Carbonate Cores

Abstract: We have performed a miscible CO 2 flood study using fractured and unfractured carbonate cores and 31° API west Texas oil to evaluate oil recovery under three main injection modes: SWAG, WAG, and CGI. For each injection mode, three cases were considered: unfractured, one horizontal fracture and two fractures (one horizontal and one vertical). Increasing the number of fractures will investigate different shape factors such as the elongated slab and sugar cube models. Then, a commercial simulator was used to matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The continuous miscible CO 2 flooding shows the highest oil recovery of 73.44% OOIP after injection of about 5 pore volumes of CO 2 , Figure 4. This observation agrees with published work on sandstone, chalk, and limestone ( K u l k a r n i and Rao, 2005; Karimaie et al, 2008;and Aleidan et al, 2011). Continuous brine flooding shows about 52% OOIP after injecting 12 pore volumes of water which is comparable to some published work on carbonate cores (Aleidan and Mamora, 2010).…”
Section: Effect Of Wag Ratio On Oil Recoverysupporting
confidence: 92%
“…The continuous miscible CO 2 flooding shows the highest oil recovery of 73.44% OOIP after injection of about 5 pore volumes of CO 2 , Figure 4. This observation agrees with published work on sandstone, chalk, and limestone ( K u l k a r n i and Rao, 2005; Karimaie et al, 2008;and Aleidan et al, 2011). Continuous brine flooding shows about 52% OOIP after injecting 12 pore volumes of water which is comparable to some published work on carbonate cores (Aleidan and Mamora, 2010).…”
Section: Effect Of Wag Ratio On Oil Recoverysupporting
confidence: 92%
“…Several field case studies have shown the successful management of the CO 2 ‐EOR process both above and below the minimum miscibility pressure 11,14,34 . Water alternating gas (WAG) injection has also been considered as another means of enhancing oil recovery after primary production 35–38 . Furthermore, CO 2 can be potentially stored in the depleted reservoir after the EOR phase as a strategy to reduce the amount of greenhouse gases in the atmosphere 34,39 .…”
Section: Introductionmentioning
confidence: 99%
“…Screening methods (such as analytical and numerical analysis) 34,39,56,57 have been used to evaluate the efficiency of each step. In this case, numerical and analytical methods provide tools to evaluate the effect of specific parameters on EOR and CO 2 ‐storage performance including the effect of miscibility on CO 2 ‐EOR performance, 41,50,58–61 different injection strategies, 35 wettability and hysteresis, 49,52,62 fracture–matrix interaction, 25 and CO 2 ‐EOR and storage efficiency 34,36,63–71 …”
Section: Introductionmentioning
confidence: 99%
“…Because the gas is in bubbles,t he gas flow can be easily controlled and the poor volumetric sweep efficiency problem can be remedied. [8][9][10][11] As foam is injected into place, it can block the high-permeability layer first and divert subsequent fluid into al ow-permeability layer. However, bubbles are unstable both thermodynamically and kinetically.F oams can be stabilized either by surfactantd issolved in the liquidp hase or by as mall solid phase dispersed in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%